Analisis Potensi Pengembangan Energi Terbarukan Di Kabupaten Sumbawa Menggunakan HOMER 3.14 Untuk Projek 25 Tahun Ke Depan: Potensi Energi Terbarukan di Kabupaten Sumbawa - Arief Budiman; Indra Darmawan; Muhammad Hidayatullah; Ahmad Jaya (Jurnal Altron, 2023)
Renewable energy potential if it is used for the development of a power generation system to supply the needs of the electricity load, especially in Sumbawa Regency for the next 25 years, can be simulated using software. The purpose of this study was to determine the potential of EBT as an alternative supply of Sumbawa's electricity needs. The research method used is a quantitative method in the form of secondary data collection from BMKG and PLN then analyzed using software HOMER 3.14. So that simulation modeling and calculations can be carried out for the potential for the next 25 years. From the modeling that has been done, the sensitivity of the received solar radiation is large Solar Cell around 5.59 kWh//day and the average wind speed on the turbine is 5 m/s Net Present Cost (NPC) as big Rp.717,113,700,000 and Cost of Energy (COE) Rp. 1,191.19. This means that this modeling can generate profits for PLN of Rp.7.666.946.930 per year.